Evaluation of concrete self-healing with different insertion techniques of chemical and bacterial solutions - Pacheco, Fernanda; Loeff, Amanda; Muller, Vinicius; Zamis Ehrenbring, Hinoel; Christ, Roberto; Modolo, Regina; de Oliveira, Maria Fernanda; Tutikian, Bernardo (Revista ALCONPAT, 2022)
This study evaluated the self-healing potential of concrete with chemical and bacterial solutions encapsulated in different materials. The encapsulating materials were expanded clay (EC) and expanded perlite (EP). Self-healing effectiveness was evaluated visually with a high-precision optical microscope and 3D microtomography. Results pointed to improved performance of bacterial solutions encapsulated in expanded clay (BAC.EC) which were able to heal fissures of 0.57 mm. In contrast, bacterial solutions encapsulated in expanded perlite (BAC.EP) and sodium silicate replacing water during molding (SS) healed fissures of 0.16 mm and 0.29 mm, respectively.